National Stakeholder Engagement Workshop for Sustainable Agricultural Planning and Climate Adaptation in Malawi - Moyo, Martin; Botoman, Lester; Pungulani, Lawren; Phiri, Dean K. (CGIAR, 2025)
The International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) Malawi successfully convened a one-day stakeholder engagement workshop on 1st October 2025 at Lingadzi Inn in Lilongwe as part of its Sustainable Farming Program. The primary objective of the workshop was to bring together key actors and stakeholders across Malawi’s agriculture sector to collaboratively develop a practical and actionable sustainable farming systems plan. This plan is intended to enhance climate adaptation and build resilience among vulnerable farming communities, promoting long-term sustainability in agricultural practices. The workshop was attended by a total of 23 participants, comprising 19 males and 4 females, who represented a diverse range of institutional stakeholders actively involved in the program’s implementation. Among the attendees were representatives from the Department of Agricultural Research Services (DARS), District-level Department of Agricultural Extension Services from Mzimba, Kasungu, Balaka, and Zomba, the Lilongwe University of Agriculture and Natural Resources (LUANAR), the Department of Land Resources and Conservation, the Department of Crop Development, ICRISAT as well as regional partners including the International Institute of Tropical Agriculture (IITA) Malawi and CIAT Malawi. The technical sessions commenced with an introductory remark from the Country Representative of ICRISAT Malawi, setting the stage for the day’s discussions. This was followed by a series of insightful presentations beginning with Dr. Martin Moyo, who provided a comprehensive overview and recap of the Sustainable Farming Science Program. Subsequent presentations were delivered by experts including Dr. Botoman from ICRISAT, Dr. Pungulani representing DARS, Dr. Phiri from LUANAR, and representatives from districts identified as key climate risk areas. The workshop concluded with plenary discussions, allowing participants to exchange ideas, raise concerns, and collectively contribute to refining the strategies for Sustainable Agricultural Planning and Climate Adaptation in Malawi. “By bringing all stakeholders to the same table, Malawi can turn climate risks into opportunities, shaping agricultural systems that protect our soils, nourish our people, and safeguard the future for generations to come.”